2011
DOI: 10.1007/s11357-011-9318-1
|View full text |Cite
|
Sign up to set email alerts
|

Human common carotid wall shear stress as a function of age and gender: a 12-year follow-up study

Abstract: Hemodynamic forces play a role in the development of atherosclerosis. Their variations with age have been assessed in cross-sectional, but not longitudinal, studies. The aim of the present study was to investigate in both sexes the age-dependent change in wall shear stress and arterial stiffness in subjects studied twice 12 years apart. Forty-eight subjects (15 women and 33 men) were studied twice 12 years apart. Subjects underwent blood viscosity measurement and echo-Doppler of carotid arteries, from which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 26 publications
3
40
3
Order By: Relevance
“…In addition, the present results expand our previous prospective data on the relationship between shear stress and intima-media thickness in the same population [16]; in the present data, established carotid atherosclerosis has been considered; tensile forces have been taken into account, and the asymmetric atherosclerosis model has ruled out many possible confounding factors.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In addition, the present results expand our previous prospective data on the relationship between shear stress and intima-media thickness in the same population [16]; in the present data, established carotid atherosclerosis has been considered; tensile forces have been taken into account, and the asymmetric atherosclerosis model has ruled out many possible confounding factors.…”
Section: Discussionsupporting
confidence: 75%
“…The reproducibility of the measurements has been previously reported, including in terms of coefficients of variations [4,16]. In summary, the haemodynamic data of 36 subjects who participated in the baseline examination were compared to 36 new subjects matched for age, sex and cardiovascular risk factors: no significant differences were detected regarding blood viscosity and velocity, arterial diameter, and shear stress.…”
Section: Reproducibilitymentioning
confidence: 90%
See 2 more Smart Citations
“…In vitro studies have demonstrated that unidirectional high shear stress induces the expression of antiatherogenic genes (i.e., endothelial nitric oxide synthase and superoxide dismutase) and inhibits the expression of atherogenic genes (i.e., vascular cell adhesion molecule, intercellular adhesion molecule, and endothelin-1), whereas retrograde shear and/or low mean shear promote a proatherogenic phenotype [24]. A previous follow-up study reported that decreases in mean carotid artery shear stress correlated with increases in carotid artery IMT [25]. In peripheral conduit arteries, acute and chronic increases in antegrade shear have beneficial effects on arterial function [12,13,26], whereas acute and chronic increases in retrograde shear are associated with endothelial dysfunction [14,15,27].…”
Section: Discussionmentioning
confidence: 99%